Relationship between Nutrition Knowledge and Physical Fitness in Semiprofessional Soccer Players - P. T. Nikolaidis; E. Theodoropoulou (Scientifica)
Whereas nutrition has a crucial role on sport performance, it is not clear to what extent nutrition knowledge is associated with physical fitness. The aim of this study was to examine the current level of nutrition knowledge of soccer players and whether this level is associated with physical fitness. Soccer players (n=185, aged 21.3±4.9 yr, weight 72.3±8.4 kg, and height 177.5±6.4 cm) performed a battery of physical fitness tests (sit-and-reach test, SAR; physical working capacity in heart rate 170, PWC170; and Wingate anaerobic test, WAnT) and completed an 11-item nutrition knowledge questionnaire (NKQ). Low to moderate Pearson correlations (0.15<r<0.34, p<0.05) of NKQ with age, weight, height, fat free mass (FFM), SAR, peak power, and mean power of WAnT were observed. Soccer players with high score in NKQ were older (4.4 yr (2.2; 6.6), mean difference (95% confidence intervals)) and heavier (4.5 kg (0.6; 8.3)) with higher FFM (4.0 kg (1.1; 6.8)) and peak power (59 W (2; 116)) than their counterparts with low score. The moderate score in the NKQ suggests that soccer players should be targeted for nutrition education. Although the association between NKQ and physical fitness was low to moderate, there were indications that better nutrition knowledge might result in higher physical fitness and, consequently, soccer performance.